Influence of the Novel Histamine H3 Receptor Antagonist/Inverse Agonist M39 on Gastroprotection and PGE2 Production Induced by (R)-Alpha-Methylhistamine in C57BL/6 Mice - Bastaki, Salim M. A.; Amir, Naheed; Więcek, Małgorzata; Kieć-Kononowicz, Katarzyna; Sadek, Bassem (Frontiers in Pharmacology, 2019)
The role of histamine H3 receptors (H3Rs) in the regulation of gastroprotection and production of prostaglandin E2 (PGE2) as well as somatostatin remains contradictory. Therefore, objective of the current study was to determine whether antagonist/inverse agonist of H3Rs mediate protective action in the C57BL/6 mice by using in vivo model of the acidified ethanol-induced gastric ulcers and gastric acid secretion. The results showed that acute systemic administration of H3R agonist (R)-alpha-methylhistamine (RAMH, 100 mg/kg, i.g.) significantly reduced both the severity of macroscopically assessed ulcer index and increased mucosal PGE2 production without any alteration of somatostatin concentration in gastric juice(all P<0.05). However, only acute systemic administration of the H2R agonist dimaprit (DIM, 10 mg/kg, p.o.) significantly decreased the level of somatostatin measured in gastric juice (P<0.05). On the contrary, the H3R agonist RAMH significantly increased gastric acid output (P<0.05). Moreover, acute systemic administration of H3R antagonist/inverse agonist M39 with high in vitro H3R antagonist affinity (hH3R pKi=7.62), high selectivity profile, and high in vivo H3R antagonist potency (ED50 = 2.7 + 1.0 mg/kg, p.o.) dose-dependently (0.3-3 mg/kg, i.g.) abrogated the RAMH-induced increase of acid output (P<0.05), but not the DIM (10 mg/kg, i.g.)-stimulated acid secretion, indicating that RAMH as well as M39 modulate the gastroprotective effects through interactions with histamine H3Rs. In addition, the RAMH-induced increase in PGE2 production was reversed when mice were pretreated with M39 (0.3 mg/kg, o.p.) (P<0.05), demonstrating that changes in histamine and gastric acid secretion induced by the activation of H3Rs were reflected in alterations of PGE2 biosynthesis. The present findings indicate that H3Rs are profoundly involved in the maintenance of gastric mucosal integrity by modulating PGE2 as well as gastric acid secretion, with no apparent role in the regulation of the inhibitory influence of somatostatin.